2006
DOI: 10.1161/01.str.0000199064.94588.39
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble Administration Accelerates Clot Lysis During Continuous 2-MHz Ultrasound Monitoring in Stroke Patients Treated With Intravenous Tissue Plasminogen Activator

Abstract: Administration of MBs induces further acceleration of US-enhanced thrombolysis in acute stroke, leading to a more complete recanalization and to a trend toward better short- and long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
300
5
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(327 citation statements)
references
References 29 publications
11
300
5
11
Order By: Relevance
“…Next to diagnostic applications, randomized clinical studies suggest therapeutic efficacy of ultrasound on recanalization of acute cerebral artery occlusion in terms of an acceleration of fibrinolysis with recombinant tissue-type plasminogen activator (rt-PA) (Alexandrov et al, 2004;Eggers et al, 2008). Echo contrast agents may further improve treatment efficacy (Molina et al, 2006;Perren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Next to diagnostic applications, randomized clinical studies suggest therapeutic efficacy of ultrasound on recanalization of acute cerebral artery occlusion in terms of an acceleration of fibrinolysis with recombinant tissue-type plasminogen activator (rt-PA) (Alexandrov et al, 2004;Eggers et al, 2008). Echo contrast agents may further improve treatment efficacy (Molina et al, 2006;Perren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound enhances thrombolysis, particularly when applied in conjunction with intravenous administration of thrombolytic agents [45][46][47].Microbubble oscillation has also been shown to enhance the breakup of a clot, with maximal efficacy achieved with the combined effect of insonation, thrombolytic agents and microbubbles [46,47].Challenges for clinical translation include the development of systems for reliable control of the applied ultrasound dose and the great challenges of achieving the required timely intervention (3-6h after the thrombus formation) in the critical applications of stroke and myocardial infarction.…”
Section: Applicationsmentioning
confidence: 99%
“…These authors observed an increase in the rate of sustained complete recanalization within 2 h after the administration of rt-PA in those patients receiving the combined therapy. Building on this strategy for therapeutic success, Molina et al administered galactose-based microbubbles (Levovist™) in combination with 2.0-MHz transcranial Doppler ultrasound during rt-PA therapy and observed a further increase in the rate of complete recanalization [25]. However, another study carried out in patients using 300-kHz transcranial ultrasound with a spatial peak temporal average intensity of 0.7 W/cm 2 in combination with rt-PA demonstrated an increased rate of cerebral hemorrhage and the study was prematurely stopped [26].…”
Section: Introductionmentioning
confidence: 99%